The neuromodulatory effects of flavonoids and gut Microbiota through the gut-brain axis - Wang, Haoran; Zhao, Tingting; Liu, Zhenjiang; Danzengquzhen; Cisangzhuoma; Ma, Jinying; Li, Xin; Huang, Xiaodan; Li, Bin (Frontiers in Cellular and Infection Microbiology, 2023)
Recent investigations show that dietary consumption of flavonoids could potentially confer neuroprotective effects through a variety of direct and indirect mechanisms. Numerous flavonoids have been shown to cross the BBB and accumulate within the central nervous system (CNS). Some of these compounds purportedly counteract the accumulation and deleterious effects of reactive oxygen species, fostering neuronal survival and proliferation by inhibiting neuroinflammatory and oxidative stress responses. Moreover, several studies suggest that gut microbiota may participate in regulating brain function and host behavior through the production and modulation of bioactive metabolites. Flavonoids may shape gut microbiota composition by acting as carbon substrates to promote the growth of beneficial bacteria that produce these neuroprotective metabolites, consequently antagonizing or suppressing potential pathogens. By influencing the microbiota-gut-brain axis through this selection process, flavonoids may indirectly improve brain health. This review examines the current state of research into the relationship between bioactive flavonoids, gut microbiota, and the gut-brain axis.